The establishment of the industry's profile and identification of competitive strategies for small and medium logistics service providers / Mohamad Zulfadhli Jusoh - Jusoh, Mohamad Zulfadhli (2016)
The rise of free trade around the world is the implication of the technological evolution, globalisation, and liberalisation. Numerous numbers of companies are strategically exploring the potential business plans to retain and expand their businesses in the challenging market environment. Therefore, the market becomes more competitive due to the competition to survive and succeed in the business. All companies need to deal with difficult and different challenges in the market, especially the small and medium enterprises (SMEs). The logistics industry as the key element that provides logistics activities to other industries has been seen as could be affected by the ASEAN services liberalisation. This study intended to explore how the SMEs react to the competition in the market during services liberalisation through the business strategies. The key target of this study was to establish the current profile of the Malaysian logistics SMEs and the type of business strategies that are most adopted by the SMEs. Besides that, the awareness of the ASEAN services liberalisation among the Malaysian logistics SMEs was also highlighted in this study. Therefore, in meeting the objectives of this study, a mixed methods was adopted and the data used in this study were derived from quantitative and qualitative analyses. The quantitative data were a set of registered logistics companies that were bought from the Department of Statistics Malaysia (DOSM) while the qualitative data were from interview sessions that were conducted to identify the awareness and business strategies adopted by the SMEs. The results advocate that from the analyses, the profile of the Malaysian logistics SMEs is very important to the government agencies, industry, and academics. Other than that, this study also presented that the awareness of the SMEs towards the ASEAN services liberalisation is still lacking. In addition, it is equally pointed out that most SMEs utilise a combination of Porter's generic strategies to retain and compete in the market. This study also found that the Malaysian logistics SMEs adopted the combined business strategies to remain competitive in the market. For this reason, it is strongly indicated that Porter's generic strategies are still relevant to the Malaysian logistics SMEs in facing the globalisation and liberalisation challenges.